Revolutionary lives of the Red and Black Atlantic since 1917 - Rice, Alan J., 1960-; Hogsbjerg, Christian; Featherstone, David, 1974- (Book collections on Project MUSE., 2022)
This volume explores the life histories of a wide range of radical figures whose political activity in relation to the black liberation struggle was catalysed or profoundly shaped by the global impact and legacy of the Russian Revolution of 1917, including C.L.R. James, Paul Robeson, Walter Rodney and Grace P. Campbell.